Strategi Kepala Sekolah dalam Meningkatkan Sarana dan Prasarana untuk Menunjang Inovasi Pembelajaran di Sekolah SMA Negeri 1 Binjai Kabupaten Langkat Tahun Ajaran 2024-2025 (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this paper is to determine the tactics used by the principal of SMA Negeri 1 Binjai, Langkat Regency, in maximizing school infrastructure and facilities to encourage innovative learning. Respondents in this paper were the principal and teachers. This study employed a qualitative descriptive methodology. Structured interviews were used as data collection instruments. The results showed that the principal used a priority scale and school quality reports in the field of facilities and infrastructure as the main guidelines in designing strategies for improving school facilities. These strategies include thorough planning, effective budget management, and the involvement of all school members in the decision-making process. These efforts were made to ensure that the available facilities and infrastructure are able to support innovative learning needs and are in line with current developments. The quality of learning innovation at SMA Negeri 1 Binjai is closely related to the principal's strategy in improving facilities and infrastructure. This is because the innovative learning process requires the support of adequate facilities, such as comfortable classrooms, complete laboratories, technology-based learning media, and a conducive learning environment. The effectiveness of the principal's plan to improve facilities and infrastructure is greatly influenced by several factors, including teacher involvement in planning, the principal's managerial skills, the availability of School Operational Assistance (BOS) funds, and collaboration among all school personnel. With good synergy between various parties, it is hoped that innovation in learning can run optimally, thereby improving the quality of education at SMA Negeri 1 Binjai, Langkat Regency.